Impact of the Number of Harrowing Times on Draft Force, Soil Fragmentation, and Bulk Density under Different Forward speeds and Depths - Abdul Hussein, Abbas (University of Thi-Qar Journal of agricultural research, 2025)
A field experiment was conducted in one of the fields of the Faculty of Agriculture, Karma Ali site, on clay soil, according to a Randomized Complete Block Design (RCBD). The plowing process was performed with a disk plow and harrowing with a disk harrow once, twice, and three times, while the plowing depth of  15, 20, and 25 cm, and the forward speed levels of  2.58, 4.03 and 5.57 km h-1. The results showed that the draft force required by the disk plow used in the plowing process was higher than the traction force required by the draft ged disk harrow used in the harrowing process by a percentage of 10.11, 10.87, and 11.67% in the case of harrowing once, twice, and three times, respectively. The traction force also decreased with increasing harrowing times, as when Increasing the tillage from once to twice and three times decreased the draft force by 15% and 32% respectively. The number of tillage times, once, twice and three times, was significantly superior in reducing the values ​​of the crumbling index and apparent density compared to the plowing process, as the plowing process recorded the highest draft force and the highest values ​​of the crumbling index and apparent density of 14.95 kN, 42.02 mm and 1.35 Mg m-3 respectively. The results also showed the significant interaction between the tillage and the plowing depth in reducing the draft force, crumbling index and apparent density compared to the plowing process. The lowest crumbling index and lowest draft force were at a depth of 15 cm and three times of 14.76 mm and 2.89 kN respectively. The lowest apparent density was 1.09 g.cm-3 at a depth of 15 cm and two times of harrowing. As for the interaction between the plowing and harrowing process and the forward speed, the speed was recorded The forward speed of 2.58 km h-1 and the three-time harrowing operation recorded the lowest draft force of 2.96 kN and the lowest pulverization index at a forward speed of 5.57 km h-1 and three-time harrowing operations of 15.39 mm. The forward speed of 15.57 km h-1 and two-time harrowing operations recorded the lowest apparent density of 1.07 Mg m-3.